Utilising Facebook groups to enhance face-to-face classes / Noorzaina Idris - Idris, Noorzaina (2016)
This study examines the perceptions of TESL Undergraduates in the Faculty of Education, UiTM Shah Alam, on the use of Facebook closed groups to supplement their face-to-face classes. The data are obtained from two sources which are the surveys and interviews of the respondents. The findings indicate that 54.4% the respondents dislike participating in the Facebook group. However, 77.2% of the respondents claim that they accessed the links and files that their lecturer posted in the group while 75.5% agree that Facebook can be an effective online study group. In addition, 79.5 % agree that Facebook helps them to ask questions about their studies, assignments and so on. Moreover, 61.4% wanted their lecturer to participate more in the Facebook group and 54.4% agree that some kind of incentives should be given to encourage them to participate in the online Facebook group discussions. Thus, this indicates that if the lecturers guide them and give some incentives, the respondents are willing to participate in the Facebook group. Furthermore, the findings from the interviews triangulated the findings from the surveys. In other words, what the respondents claim in the survey are also reflected in the interviews.